Connexin expression and gap-junctional intercellular communication in ES cells and iPS cells - Oyamada, Masahito; Takebe, Kumiko; Endo, Aya; Hara, Sachiko; Oyamada, Yumiko (Frontiers in Pharmacology, 2013)
Pluripotent stem cells, i.e., embryonic stem (ES) and induced pluripotent stem (iPS) cells, can indefinitely proliferate without commitment and differentiate into all cell lineages. ES cells are derived from the inner cell mass of the preimplantation blastocyst, whereas iPS cells are generated from somatic cells by overexpression of a few transcription factors. Many studies have demonstrated that mouse and human iPS cells are highly similar but not identical to their respective ES cell counterparts. The potential to generate basically any differentiated cell types from these cells offers the possibility to establish new models of mammalian development and to create new sources of cells for regenerative medicine. ES cells and iPS cells also provide useful models to study connexin expression and gap-junctional intercellular communication (GJIC) during cell differentiation and reprogramming. In 1996, we reported connexin expression and GJIC in mouse ES cells. Because a substantial number of papers on these subjects have been published since our report, this Mini Review summarizes currently available data on connexin expression and GJIC in ES cells and iPS cells during undifferentiated state, differentiation, and reprogramming.